2007
DOI: 10.1037/cp2007007
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory, eyewitness reports, and public policy.

Abstract: In the first part of this article I summarize the source-monitoring perspective on the cognitive processes involved in differentiating between mental events from different sources (e.g., memories of what one witnessed during a crime versus memories of what one later heard a cowitness describe). In the middle section of the article I consider, from the perspective of the source-monitoring framework, four issues pertaining to remembering in forensic situations: 1) adults' memory reports, 2) children's memory rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…However, although the young group gave more accurate accounts (Experiment 1), the reporting accuracy was also very high for the very young group (97% vs. 92% in Experiment 1; 95% vs. 90% in Experiment 2). Concerning resistance to suggestions, consistent with previous research (see Ceci & Bruck, 1998;Lindsay, 2007), the very young children were more influenced (yes/misled) by, but also, less resistant (no/not misled) to misleading questions (which suggested incorrect information) than were the young children (Experiments 1 and 2). Our results concerning the children's free recall and suggestibility provided us with an answer to these two questions: What is the influence of the CI and its variations on children's statements?…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, although the young group gave more accurate accounts (Experiment 1), the reporting accuracy was also very high for the very young group (97% vs. 92% in Experiment 1; 95% vs. 90% in Experiment 2). Concerning resistance to suggestions, consistent with previous research (see Ceci & Bruck, 1998;Lindsay, 2007), the very young children were more influenced (yes/misled) by, but also, less resistant (no/not misled) to misleading questions (which suggested incorrect information) than were the young children (Experiments 1 and 2). Our results concerning the children's free recall and suggestibility provided us with an answer to these two questions: What is the influence of the CI and its variations on children's statements?…”
Section: Discussionsupporting
confidence: 79%
“…It is now well documented that children under the age of 6, in comparison to older children, are highly sensitive to the influence of adults (Ceci & Bruck, 1998;Geddie, Fradin, & Beer, 2000;Greenstock & Pipe, 1996;Lindsay, 2007). However, the link between age and suggestibility may be not that linear (e.g.…”
Section: The Cognitive Interview and Child Suggestibilitymentioning
confidence: 99%
“…Seamon et al, 2006). Consistent with the SMF, imagery scripts that emphasize perceptual and contextual detail may be especially likely to induce memory errors because the presence of these kinds of cues often signal that a memory might be based on an event directly experienced (Gonsalves, Reber, Gitelman, Parrish, Mesulam, & Paller, 2004;Johnson et al, 1993;Lindsay, 2008a). More elaborate imagery scripts emphasizing perceptual details do indeed exaggerate imagination inflation effects (Thomas et al, 2003).…”
Section: Implications For Debates About Guided Imagerymentioning
confidence: 80%
“…Failures of contextual memory can have very serious consequences in some situations, such as when a witness identifies a suspect in a criminal case (Lindsay, 2007). For example, a substantial body of research has shown that searching mugshots after witnessing a crime is very harmful to later lineup identifications (Deffenbacher, Bornstein, & Penrod, 2006).…”
Section: Discussionmentioning
confidence: 99%